Chapter Русский перевод книги Антуана де Плювинеля L'Instruction du Roy / Reitkunst с немецкого языка - Maier, Ingrid (Frank & Timme, 2022)
In the second half of the 17th century, the translators of the Russian ambassadorial office had to translate a large number of books. Among them, the equestrian books by Antoine de Pluvinel from the 1620s stand out: Maneige Royal and L'Instruction du Roy / Reitkunst. Ingrid Maier focuses on the Russian translation of L'Instruction du Roy / Reitkunst from 1677, but the history of this edition is inseparable from that of Maneige Royal. The author compares selected fragments of the translations. Even this first selective analysis leads to surprising insights into translation techniques and the translators' interventions in the texts.